Sintesis Hidroksiapatit Dari Limbah Tulang Sapi Menggunakan Metode Presipitasi Dengan Variasi Rasio Ca/P Dan Konsentrasi H3PO4 - Yenti, Silvia Reni; Haris, Al; Fadli, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Hydroxyapatite is a compound of calcium phosphate ceramics and also the main inorganic components in bones and teeth of animals and humans. Hydroxyapatite was synthesized from bovine bones using precipitation method. The purpose of this study is to determine the effect of the ratio of Ca / P and the concentration of H3PO4 to the characterization of hydroxyapatite made from bovine bones as raw materials using precipitation method. Bovine bones were calcined at 1000℃ to produce calcium oxide (CaO). Then CaO was dissolved into distilled water and slowly mixed with phosphoric acid (H3PO4) at a ratio of Ca/P 0.67; 1.67; 2.67 and the concentration of H3PO4 0.6 M, 0.8 M, 1.2 M and 2.4 M. Then the mixture going through aging process for 24 hours and then the precipitate was filtered. The residue was calcined and characterized by XRD, FTIR, and SEM-EDX. Hydroxyapatite with a variation of Ca/P ratio, the difference between the initial and final ratio of Ca/P tends to decrease with an increase of the initial ratio of Ca/P. Hydroxyapatite with a variation of H3PO4 concentration, the final ratio of Ca/P tends to decrease with an increase of H3PO4 concentration.Keywords: hydroxyapatite, precipitation, ratio, concentration.